Distribution of bird communities in University of Lampung, Indonesia - Dian Iswandaru; Novriyanti Novriyanti; Irwan Sukri Banuwa; Sugeng P. Harianto (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Iswandaru D, Novriyanti N, Banuwa IS, Harianto SP. 2020. Distribution of bird communities in University of Lampung, Indonesia. Biodiversitas 21: 2629-2637. University of Lampung (UNILA), Indonesia holds a variety of potential biodiversity, especially birds, species that are sensitive to environmental changes. It is necessary to detect early bird communities spread across UNILA before the physical of this higher institution of education (including vegetation distribution that supplies birdlife) begins to change even further. The method used is the Field Method and Concentration Count Method. Research and Experimental Garden (ST1), Integrated Field Laboratory (ST2), Soccer Field (ST3), Deer Breeding (ST4), Arboretum and Green Lane (ST5) were observed for 2 months. The results showed that 37 bird species from 21 families and 8 orders were spread in each study location. The Passeriformes group dominated in all five study sites with the number of species and the number of families reaching 57% of all species found. Most bird communities (individuals, species, and families) can be found in the Integrated Field Laboratory (ST2) compared to the other four locations. Diversity index numbers (H '), Evenness (E), and Dominance (D) types at this location also support it even though the overall results of the analysis show that the distribution of bird species is evenly distributed and that no bird species dominate in community building.